Tocilizumab Induces Rapid, Sustained Improvement of Inflammatory Markers in COVID-19, With Clinical Improvement in Most Patients. (September 2021) - Morin, Scott J.; Jani, Chinmay; Rupal, Arashdeep; Singh, Harpreet; Bourque, Daniel; Colgrove, Robert C.
Abstract : Supplemental Digital Content is Available in the Text.